2015
DOI: 10.3310/hta19430
|View full text |Cite
|
Sign up to set email alerts
|

The use of measures of obesity in childhood for predicting obesity and the development of obesity-related diseases in adulthood: a systematic review and meta-analysis

Abstract: BackgroundIt is uncertain which simple measures of childhood obesity are best for predicting future obesity-related health problems and the persistence of obesity into adolescence and adulthood.ObjectivesTo investigate the ability of simple measures, such as body mass index (BMI), to predict the persistence of obesity from childhood into adulthood and to predict obesity-related adult morbidities. To investigate how accurately simple measures diagnose obesity in children, and how acceptable these measures are t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
249
0
14

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 318 publications
(274 citation statements)
references
References 192 publications
11
249
0
14
Order By: Relevance
“…Given that 90% of the children/youth in the present study 257 were 12 years of age or older, our findings suggest that more than a quarter of adolescents with ID 258 participating in Special Olympics in the EU are overweight/obese. This is particularly troubling since 259 childhood obesity status moderately predicts adult obesity status, and the persistence of obesity from 260 adolescence to adulthood is high (Simmonds et al 2015). Research to elucidate factors contributing to 261 these high rates of obesity in young people with ID is urgently needed.…”
Section: Health 255mentioning
confidence: 99%
“…Given that 90% of the children/youth in the present study 257 were 12 years of age or older, our findings suggest that more than a quarter of adolescents with ID 258 participating in Special Olympics in the EU are overweight/obese. This is particularly troubling since 259 childhood obesity status moderately predicts adult obesity status, and the persistence of obesity from 260 adolescence to adulthood is high (Simmonds et al 2015). Research to elucidate factors contributing to 261 these high rates of obesity in young people with ID is urgently needed.…”
Section: Health 255mentioning
confidence: 99%
“…However, BMI was found to be reasonably good for diagnosing obesity during childhood [3]. The BMI is a very popular measurement because it is simple.…”
Section: Introductionmentioning
confidence: 99%
“…According to the National Cancer Institute, an estimated 84,000 annual cancer cases are linked to obesity [73] . With rising obesity rates among young children in particular, it is becoming really important to understand this link [73] .…”
Section: Discussionmentioning
confidence: 99%
“…According to the National Cancer Institute, an estimated 84,000 annual cancer cases are linked to obesity [73] . With rising obesity rates among young children in particular, it is becoming really important to understand this link [73] . Research has confirmed this perceptual shift, concluding that overweight/obese children are now nearly 25% less likely to be perceived as overweight compared to the previous decade [73] .…”
Section: Discussionmentioning
confidence: 99%